2022
DOI: 10.1002/ppap.202200086
|View full text |Cite
|
Sign up to set email alerts
|

Study of plasma parameters and gas heating in the voltage range of nondischarge to full‐discharge in a methane‐fed dielectric barrier discharge

Abstract: Experimental data are used in theoretical models to study the effects of input voltage and gas flow rate on plasma and background gas parameters in a voltage range where the transition from nondischarge to full-discharge happens. To this end, a specific methane-fed dielectric barrier discharge is used as a plasma reactor, and electrical modeling, the Boltzmann equation Plasma Process Polym. 2022;e2200086 www.plasma-polymers.com

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…This is likely because objects with sharper edges tend to have a higher charge density. [71] Enhancement of the electrical field and charge density in this reactor is calculated in the report of the Pourali et al [33] The μ-tip with similar characteristics is already employed as charged injectors in field emission devices.…”
Section: Optical Propertiesmentioning
confidence: 82%
See 1 more Smart Citation
“…This is likely because objects with sharper edges tend to have a higher charge density. [71] Enhancement of the electrical field and charge density in this reactor is calculated in the report of the Pourali et al [33] The μ-tip with similar characteristics is already employed as charged injectors in field emission devices.…”
Section: Optical Propertiesmentioning
confidence: 82%
“…Where T in the equation is for the time period (1/Frequency), I p is for plasma current, V p is for voltages across the plasma gap, I m is the monitoring current across in the current transformer and V s the total applied voltage. The calculations and further information can be found in the study conducted by Pourali et al [51] P…”
Section: Results and Discussion Electrical Propertiesmentioning
confidence: 99%
“…The high heating at the tip of the pyramids causes a higher rotational temperature in the pyramid electrode DBD. High electric fields produce more heating due to the joule heating, [ 20 ] so near the sharp points there is more gas heating which results in more increase in rotational temperature. In pyramid electrode DBD, near the sharp point ions are accelerated due to the high intensity of the electric field and their drift velocity is high.…”
Section: Resultsmentioning
confidence: 99%
“…The experimental set‐up was presented in our previous work. [ 20 ] A 400 pF external capacitor was connected to the ground line to monitor the generated electric charges (Q) in the plasma. A high‐voltage power generator (G2000 Redline Technologies) was used as an electrical power source that generates different amplitudes of the sinusoidal wave with various frequencies.…”
Section: Experimental Setup and Methodologymentioning
confidence: 99%
“…where A is the area of the electrode, 2.99⋅10 − 4 m 2 , T is the gas temperature and T s is the temperature of the electrode surface. In our previous studies, we recognized the need to characterize the temperature of the gas and therefore a detailed measurement of CO 2 rotational temperature in the micro DBD reactor was performed and correlated with the gas temperature [17,50]. It was concluded that Eq.…”
Section: Effect Of Discharge Gap Sizementioning
confidence: 99%